2020
DOI: 10.1186/s13054-020-03418-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracorporeal membrane oxygenation in children with sepsis: a systematic review and meta-analysis

Abstract: Background The benefits of extracorporeal membrane oxygenation (ECMO) in children with sepsis remain controversial. Current guidelines on management of septic shock in children recommend consideration of ECMO as salvage therapy. We sought to review peer-reviewed publications on effectiveness of ECMO in children with sepsis. Methods Studies reporting on mortality in children with sepsis supported with ECMO, published in PubMed, Scopus and Embase fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 53 publications
0
24
1
Order By: Relevance
“…All studies written in English or with English translation, reporting on five or more adult patients (≥ 18 years) with septic shock supported with VA ECMO were included [ 18 ]. We excluded any non-human or paediatric studies, and any case reports to avoid publication bias.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies written in English or with English translation, reporting on five or more adult patients (≥ 18 years) with septic shock supported with VA ECMO were included [ 18 ]. We excluded any non-human or paediatric studies, and any case reports to avoid publication bias.…”
Section: Methodsmentioning
confidence: 99%
“…The (23,18.5%) were the most commonly reported complications while receiving ECMO. 9 studies (262 patients) reported on the pathogens cultured from the patients (Additional File 6).…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…All statistical analyses were performed in R studio (Version 4.0.5, R studio, Inc. Boston) using the ‘meta’ and ‘dmetar’ packages [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The encouraging outcomes of extracorporeal membrane oxygenation (ECMO) in paediatric septic shock have led to it being recommended as a potential therapy in some societal guidelines. [11][12][13][14][15][16][17] However, the haemodynamic pattern of septic shock is markedly different across age groups: new-born infants typically present with pulmonary hypertension and right heart failure, young children with left heart failure, and adolescents and adults with distributive shock. [15] Given the contrast in haemodynamic status between adult and paediatric shock, the use of ECMO, and in particular venoarterial ECMO (VA-ECMO), in adult septic shock remains controversial.…”
Section: Introductionmentioning
confidence: 99%